Analysis of low level laser therapy in vitro cultures of bacteria and fungi - Andraus, Rodrigo Antonio Carvalho; Maia, Luciana Prado; Santos, João Paulo Manfré dos; Mesquita, Amanda Rezende; Santos, Thaynara Gonzaga; Braoios, Alexandre; Prado, Rodrigo Paschoal (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Background: Low intensity laser therapy has been used to accelerate the ulcers healing due to its healing, anti-inflammatory, analgesic and anti-edematous effects. Contaminations by bacteria or fungi on these ulcers commonly happen, constituting a major complication of healing, but there is no consensus about laser therapy bactericidal or fungicidal effect. Aim: To analyze the effects of different times of appliantion using the 808nm and 660nm lasers on cultures of different bacterial species and fungi in vitro. Method: Photon Lase III - DMC was used, with the wavelengths of 660 and 808nm and 30mW, 60mW and 100mW of power, with different exposure time to laser irradiation. Fifteen Petri plates were prepared, 12 plates containing Gram-positive (3 Staphylococcus aureus plates, 3 nterococcus plates) and gram negative bacterias (3 Escherichia coli, 3 Klebsiella pneumonia plates) and 3 Petri plates with the fungi Candida albicans. Plates were randomly divided into 3 groups with 5 plates each group. Plates of Group 1 were irradiated with 660 nm laser at nine different points (A, A1 , A2 /B, B1 , B2 /C, C1 , C2 ), and points A/B/C reciebed only one application, points A1 ,B1 ,C1 received 2 applications and points A2 ,B2 ,C2 received 3 applications. Plates from group 2 where irradiated with 660nm also in nine diferente points, following the same criterea of group 1, while plate of group 3 where used as control, without irradiation. Groups 1 and 2 were irradiated with 144 J/cm² dose at point A (irradiation time of 2 minutes and 15 seconds), point B (irradiation time of 1 minute 7 seconds) and at point C (40 seconds). After the irradiations the plates were incubated for 24 hours. The cultures were visually examined to check the presence or not of the inhibition zone. In all the groups, no zone of inhibition nor growth were observed. Conclusion: Low intensity laser therapy (808nm and 660nm) did not produce bactericidal and/or bacteriostatic effects, and even no bio-stimulant effect on the bacteria.